POOR AND INADEQUATE ELECTRICAL POWER GENERATION, TRANSMISSION AND DISTRIBUTION IN NIGERIA: ECONOMIC, PSYCHO-SOCIAL, HEALTH, SECURITY AND EDUCATIONAL CONSEQUENCES - Omede, Jacob; Omede, Andrew Abdul (IJRDO-Journal of Applied Science, 2015)
This paper examined the consequences of poor and inadequate electricity generation, transmission anddistribution on the economic, psycho-social, health, security and educational development of Nigeriaand Nigerians. In an attempt to do this, the paper discusses the state of electricity generation,transmission and distribution in Nigeria and affirmed that it was still poor and low comparable to othernations despite efforts of government to improve it. Some of the problems responsible for theinadequate electricity supply and poor performance which the paper identified included over loadingand load shedding, poor funding, natural disasters such as rain and wind storms as well as erosions andwild fires that destroy electricity installations and also the non-diversification of energy sources toinclude solar and wind. The paper further discussed the consequences of these poor and inadequateelectricity supplies on national economic growth and development, psycho-social, health, security andthe educational growth and development of both the individuals and the nation. The paper finallyconcluded discussions by recommending among others that sources of energy be diversified to includethe use of solar and wind in addition to oil and gas, promotion of more research efforts in the sectorthrough frequent seminars and conferences and that security agents should intensify surveillance toforestall, arrest and penalize illegal exploration of oil and gas as well as destruction of oil and gasinstallations that frustrate supply of available electricity.